#TITLE_ALTERNATIVE# - YOHANA ADINDA NAIBORHU (NIM 12104045), KORY
The developments that done in North Bandung area caused some worries for the inhabitant that the source of clean water will decrease and also flood in rain season because of the area that suppose to be catchment area is no longer hold the water. For that reason, prediction of unconfined groundwater supplement zone is required. Survey of the supplement zone of unconfined groundwater in North Bandung region is a qualitative survey to analyze parameter, which support the potential of unconfined groundwater supplement. There are seven parameters used in DRASTIC method to analyze the potential of unconfined groundwater supplement, Depth to groundwater, Recharge, Aquifer media, Soil media, Topography, Impact of vadose zone, hydraulic Conductivity of aquifer media.DRASTIC method was developed by Aller (1987) and Lars Rossen (1994) to studied groundwater vulnerability level to contamination. The study was performed with parameter weighting and rating method to DRASTIC parameter. When the parameters in DRASTIC method corresponded to water balance, they increase the supplement of unconfined groundwater. Each parameter value multiplied by score and then all chart of seven factors will be overlaid in order to obtain DRASTIC index. The DRASTIC index is DwDr + RwRr + AwAr + SwSr + TwTr + IwIr + CwCr. The overlay results of seven parameters will create 15 new zones with the highest index is 110 and the lowest index is 68. Based on DRASTIC method this amount can devided into two groups as follows: 108-148 fairly potential, 67-107 less potential.